Study of clinical profile of ischemic heart disease patients admitted in tertiary care hospital - Sancheti, Poonam Vijay; Mangulikar, Suresh Konappa (International Journal Of Community Medicine And Public Health, 2017)
Background: Cardiovascular diseases have assumed epidemic proportions in India. The study was undertaken to know the clinical presentation of ischemic heart disease. It also included time lapsed between symptoms and admission which is important outcome indicator. The aim and objective was to study the clinical profile of ischemic heart disease patients admitted in tertiary care hospital. Methods: The study was done in IHD patients admitted in ICU of tertiary care hospital. The study period was June 2014 to June 2015. Detailed clinical data like symptoms, signs, associated illnesses, general and systemic examination was included. Results: 33.59% patients were brought to tertiary care centre within 3-6 hours of onset of symptoms. Out of total, 63.61% presented with chest pain not relieved in ten minutes followed by 21.89% patients who had chest pain which relieved in ten minutes. 68.95% patients had associated sweating, 35.62% had associated breathless-ness and 16.03% had associated swelling over feet. Associated symptoms with chest pain were not exclusive of each other. 62.85% patients were of STEMI, 21.37% patients were classified as NSTMI and 15.78% were patients of unstable angina. Cardiac failure was seen in 69.52% patients. Conclusions: Most of the patients were of STEMI with most common complain of chest pain and most common clinical complication was cardiac failure in the patients.